Smart technology in the home: time for more clarity - Darby, S (Taylor and Francis, 2017)
The idea of the smart home has been around for decades but smart homes (under most definitions) are extremely rare, although digital technology and automated appliances are commonplace in the more affluent regions of the world. This commentary argues that there are inherent difficulties with expectations for smart homes and with making them viable; and with definitions and roles of ‘users’ in smart systems. It considers what a smart home might be and the problems that smart homes might address, identifying two types of narrative in the smart energy literature. One centres on the highly-automated dwelling with integrated appliances, emphasising state-of-the-art technology, convenience and, in some sense, efficiency. The second narrative type focuses more on system-level issues such as peak demand, ancillary services and the spread of microgeneration, and on selective applications of information and communication technology (ICT) to address these. Both raise questions about the identity of users, nature of control, boundaries of the home and ecological impact.